Topoisomerase II α Gene as a Marker for Prognostic Prediction of Hepatocellular Carcinoma: A Bioinformatics Analysis - Lu, Jin; An, Shaoguang; Ma, Junjie; Yang, Yue; Zhang, Lei; Yu, Peng; Tao, Heng; Chen, Yunfan; Zhang, Haoxuan (Chinese medical sciences journal, 2022)
To investigate the expression of topoisomerase II α (TOP2α) in hepatocellular carcinoma (HCC) and its role in predicting prognosis of HCC patients. We used HCC-related datasets in UALCAN, HCCDB, and cBioPortal databases to analyze the expression and mutation of TOP2α and its co-expressed genes in HCC tissues. GO function and KEGG pathway enrichment of TOP2α and its co-expressed genes were identified. The TIMER database was used to analyze infiltration levels of immune cells in HCC. The impacts of TOP2α and its co-expression genes and the infiltrated immune cells on the survival of HCC patients were assayed by Kaplan-Meier plotter analysis. TOP2α and its co-expression genes were highly expressed in HCC (P < 0.001) and detrimental to overall survival of HCC patients (P < 0.001). TOP2α and its co-expression genes were mainly involved in cell mitosis and proliferation, and cell cycle pathway (ID: hsa04110, P = 0.00194S). TOP2α and its co-expression genes were mutated in HCC and the mutations were significantly detrimental to overall survival (P = 0.0247) and disease-free survival (P = 0.026S) of HCC patients. High TOP2α expression was positively correlated with the infiltration of B cell (r = 0.4S9, P < 0.01), CD8+T cell (r = 0.312, P < 0.01), CD4+T cell (r = 0.370, P < 0.01), macrophage (r = 0.459, P < 0.01), neutrophil (r = 0.405, P < 0.01), and dendritic cell (r = 0.473, P < 0.01) in HCC. The CD8+T cell infiltration significantly prolonged the 3- and 5-year survival of HCC patients (all P < 0.05), and CD4+T cell infiltration significantly shortened the 3-, 5-, and 10-year survival of HCC patients (all P < 0.05) TOP2α may be an oncogene, which was associated with poor prognosis of HCC patients and could be used as a biomarker for the prognostic prediction of HCC.